Source code: automatic C library wrapping - Ctypes from the trenches - Kloss, Guy K. (Massey University, 2009)
At some point of time many Python developers at least in computational science will face the situation that they want to interface some natively compiled library from Python. For binding native code to Python by now a larger variety of tools and technologies are available. This paper focuses on wrapping shared C libraries, using Python's default Ctypes, with the help of the matching source code generator from CtypesLib.
Keywords: Python (Programming language); Ctypes; Code generation